2017
DOI: 10.4049/jimmunol.1601068
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Basis for the Lack of Inflammatory Responses in Mouse Embryonic Stem Cells and Their Differentiated Cells

Abstract: We have previously reported that mouse embryonic stem cells (mESCs) do not have a functional IFN-based antiviral mechanism. The current study extends our investigation to the inflammatory response in mESCs and mESC-differentiated cells. We demonstrate that LPS, TNFα, and viral infection, all of which induce robust inflammatory responses in naturally differentiated cells, failed to activate NFκB, the key transcription factor that mediates inflammatory responses, and were unable to induce the expression of infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(50 citation statements)
references
References 53 publications
6
42
0
Order By: Relevance
“…19,40 In contrast, hESCs and hiPSCs barely respond to IFNβ as judged by their lack of ISG expression. 20 The lack of response to these agents is also reported by other investigators in mESCs 12,13 and in miPSCs. 44 In addition to inducing IFN response, viral RNA can directly activate double-stranded (ds) RNA-activated protein kinase (PKR) and cause inhibition of both cellular and viral protein synthesis, thereby repressing viral replication as a separate antiviral mechanism.…”
Section: Underde Veloped Innate Immunit Y Is a Common Fe Ature Of Psupporting
confidence: 59%
See 4 more Smart Citations
“…19,40 In contrast, hESCs and hiPSCs barely respond to IFNβ as judged by their lack of ISG expression. 20 The lack of response to these agents is also reported by other investigators in mESCs 12,13 and in miPSCs. 44 In addition to inducing IFN response, viral RNA can directly activate double-stranded (ds) RNA-activated protein kinase (PKR) and cause inhibition of both cellular and viral protein synthesis, thereby repressing viral replication as a separate antiviral mechanism.…”
Section: Underde Veloped Innate Immunit Y Is a Common Fe Ature Of Psupporting
confidence: 59%
“…Studies from other investigators have reported similar findings in several types of tissue cells differentiated from both hESCs and mESCs, including endothelial cells, smooth muscle cells, cardiomyocytes, and osteoblasts 12,13,16,64,65. This is elegantly demonstrated with a co-culture model in which mESCs and mESC-FBs are cultured in the same dish and subjected to identical experimental conditions 19,20,40. 19,40 At the molecular level, cytokine receptors and PRRs, such as TNFR1, TLR3, and MDA5, are upregulated in ESC-differentiated cells.…”
supporting
confidence: 54%
See 3 more Smart Citations